Determining the role of differential expression of candidate icroRNAs in cardiometabolic diseases among South African adults living with HIV - Govender, Leegan (Department of Pathology, 2025)
Background: MicroRNAs (miRNAs) are potential prognostic/diagnostic markers that have been investigated for screening of cardiometabolic disease (CMD) risk in general populations. However, little is known about their value in people living with human immunodeficiency virus (PLWH), who have an increased susceptibility to CMDs. PLWH have an increased susceptibility to CMDs because of chronic inflammation caused by a persistent immune response, metabolic complications from antiretroviral therapies, and traditional risk factors. In this study the association of differential expression of candidate miRNAs, miR-126-3p, -223-3p, and -320a with CMDs was investigated among PLWH. Methods: Using a cross-sectional study design ≥18-year-old PLWH were recruited from 17 random HIV clinics in the Western Cape, South Africa between 2014-2015. Standard international definitions were used to diagnose CMDs. Whole blood miRNAs were isolated, and expression quantified by reverse transcription quantitative polymerase chain reaction. MiRNA expression was compared between participants with a CMD and without for each investigated outcome, using Wilcoxon rank sum/Kruskal Wallis tests. Robust correlations, robust linear regressions and logistic regressions assessed miRNAs relationships with cardiometabolic risk profiles. A p-value <0.05 was considered statistically significant. Results: Among 675 participants (81% women), prevalence of CMDs/traits was: elevated highsensitivity C-reactive protein (67.4%), raised waist circumference (WC) (63.3%), obesity (34.1%), insulin resistance (IR) (9.9%), and diabetes mellitus (8.6%). Target miRNAs were not significantly differentially expressed based on individual CMD statuses. However, target miRNAs were significantly correlated with glucose homeostasis variables [fasting glucose (r≤0.129, p≤0.046); fasting insulin (r≤0.115, p≤0.015); 2-hour insulin (r≤0.097, p≤0.029); and homeostatic model assessment of insulin resistance (HOMA-IR) (r≤0.144, p≤0.002)], and miR126-3p and -223-3p were significantly correlated with alanine transaminase (r≤0.128, p≤0.022). In linear regression models after adjusted for age and gender, miR-126-3p had a borderline association with HOMA-IR (β≤0.018, p≤0.081), while miR-223-3p was borderline associated with glucose when adjusted for age, gender, and WC (β=0.001, p=0.066). There were no significant associations in logistic regression models. Conclusion: The miRNAs tested in this study appear not to be important markers for CMDs in PLWH. A genome-wide approach is recommended to uncover other miRNAs with potential as biomarkers of CMDs in PLWH.